Reflections about the faculty member in a nursing school of a public university - Merighi, Miriam Aparecida Barbosa (Revista da Escola de Enfermagem da USP, 1998)
This article is about the discussion, on the faculty member's role, who are working in a Nursing School of a Public University, attempting to suggest integration, strategies to teach and research about the nursing and the care of people, and consequently the benefits to the teachers, to the nursing school and to the nursing profession.